Variable Fluid Properties and Partial Slip Effect of MHD Flow of Nanofluids over a permeable Stretching Sheet with Heat Radiation and Viscous Dissipation - Jaber, Khaled K. (Jordan Journal of Mathematics and Statistics, 2024)
The simultaneous effects of variable fluid properties and velocity slip on a nanofluid flow over a continuously stretching semi-infinite horizontal sheet are investigated. The contribution of thermal radiation term is taken into account in the temperature equation. Viscous dissipation, Brownian motion and thermophoresis effects are taking into account. The flow is subjected to a transverse uniform magnetic field. Thermal conductivity and fluid viscosity are assumed to related linearly and inversely linear with temperature, respectively. The system of equations governed the problem is transformed into a dimensionless system of ordinary differential equations. This system is solved using shooting technique in conjunction with Rung-Kuta method. Convergence of the obtained solutions is examined. It is found that the velocity improved due to increasing θr, whereas increasing tv yields to decrease the velocity. Increasing volume fraction parameter ϕ and nanolayer thickness tv tend to reduce the temperature. We discuss in detail the effect of involved parameters on the velocity, temperature, and concentration profiles. In addition, we provide discussions and tabulated data on skin friction, Nusselt number, and Sherwood numbers.